Distribution Patterns And Species Density of Pirenella cingulata (Gmelin, 1971) In The Mangrove Forest Of Pangpang Bay, Ijen Geopark Banyuwangi Indonesia - Rendy Setiawan; Anugrah Bahtiar Triantono; Hari Sulistiyowati; Retno Wimbaningrum; Arif Mohammad Siddiq; Abdillah Baraas (Universitas Diponegoro, 2026)
Mangrove Forest Pangpang Bay is the result of a 1999 restoration work and has been classified as an Essential Economic Zone (KEE) due to its diversified area and flora and fauna. The mangrove forest of Pangpang Bay is home to Pirenella cingulata, a macro-invertebrate that is found in muddy mangrove substrates. Pirenella cingulata is a detritivore that feeds on rotting litter. This study looked at the distribution and population density of P. cingulata in the mangrove forest of Pangpang Bay, Banyuwangi. Data was collected using a 1x1 m² transect plot with diagonal placement. Data analysis for distribution patterns using the morisita index and population density was analyzed using the formula number of individuals divided by the area. Temperature, salinity, pH, and substrate type are some of the environmental characteristics observed and interpreted as supporting evidence for distribution patterns. There were 824 individuals of the P. cingulata species discovered from 120 plots in Pangpang Bay and it has a concentrated distribution. The population density was of 6.86 individuals/m², or seven individuals per 1 m². This density figure suggests a high category in Pangpang Bay. The findings of this study can be used to create management plans for the conservation of gastropods P. cingulata in the mangrove forest of Pangpang Bay